2001
DOI: 10.1038/sj.bmt.1703023
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy (HDC) and autologous hematopoietic stem cell transplantation (ASCT) as salvage therapy for relapsed osteosarcoma

Abstract: Summary:In this report, we describe our experience with highdose chemotherapy (HDC) and autologous stem cell transplantation (ASCT) in 15 children with relapsed osteosarcoma who were treated by members of the Cooperative Osteosarcoma Study Group. Eight patients received HDC after the first relapse, six patients after the second relapse and one after the sixth relapse. Thirteen patients underwent HDC and ASCT in complete remission and two patients had macroscopic tumor residues. Seven patients received HDC base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 12 publications
3
42
0
Order By: Relevance
“…However, a large number of phase-II trials including Ewing sarcomas, osteosarcomas and STS showed inconsistent results concerning outcome and benefit for the patients treated with HDCT þ PBSCT. [18][19][20][21][22][23][24][25][26] The objective of the present study was to investigate response following conventional chemotherapy with or without surgery. PFS and OS after HDCT and hematopoietic stem cell transplantation were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large number of phase-II trials including Ewing sarcomas, osteosarcomas and STS showed inconsistent results concerning outcome and benefit for the patients treated with HDCT þ PBSCT. [18][19][20][21][22][23][24][25][26] The objective of the present study was to investigate response following conventional chemotherapy with or without surgery. PFS and OS after HDCT and hematopoietic stem cell transplantation were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The few data using HDCT in the treatment of Ewing's sarcoma, osteosarcoma and rhabdomyosarcoma have demonstrated inconsistent benefits. [18][19][20][21][22] In some phase-I trials using HDCT in the treatment of patients with different histologic subtypes of adult sarcomas such as liposarcoma, leiomyosarcoma, and malignant fibrous histiocytoma long-term survivors have been reported, [23][24][25][26] but long-term survivors have also been reported with conventional chemotherapy with or without resection. 27 Whether HDCT improves the results in adult patients with bone and STS has not yet been established.…”
Section: Chemotherapy; Peripheral Blood Stem Cell Transplantationmentioning
confidence: 99%
“…9,12 Previous studies on HDCT and ASCT in osteosarcoma used heterogeneous conditioning regimens and showed varying outcomes. 3,13,14 The current analysis of high-risk osteosarcoma patients treated with HDCT and ASCT with a uniform conditioning regimen MEC at our institute showed promising results. This regimen was also promising for patients with tumor necrosis o 90% after neo-adjuvant chemotherapy as the sole factor that designated them as high-risk osteosarcoma.…”
mentioning
confidence: 99%
“…3,4,5 The tumor necrosis rate may be increased by multiple drug combinations, whereas HDC is found to be the most effective way of increasing the response rate among other conventional therapy modalities. HDC and APBSCT were reported previously to be used predominantly in metastatic osteosarcoma 7,8 and in various bone tumors with a poor prognosis. 9 In the current study, we examined the feasibility of HDC in patients with nonmetastatic, high-grade osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hovewer, peripheral blood stem cell support can decrease the myelosupressive toxicities in several tumors, including sarcomas. 6 High-dose chemotherapy (HDC) and autologous peripheral blood stem cell support or transplantation (APBSCT) were reported to be the dominant modalities used in patients with metastatic osteosarcoma 7,8 and various bone tumors with poor prognosis. 9 In the current study, we planned to harvest and transplant PBSC after two cycles of an induction chemotherapy regimen.…”
mentioning
confidence: 99%